Mental Well-Being of AIMS Students During the Pre-Pandemic: A Case Study - Monsale, Imelda; Garibay, Marianne; Jasmin, Patricia Camille (Future Science / FSH-PH Publications, 2023)
Using the Qualitative method, 25 AIMS students participated, sharing their mental health perceptions, status, and recommendations through Focus Group Discussions (FGD). Demographics show participants aged 18-22, mostly male, single, and Roman Catholic, with a significant representation from maritime programs. Clinical profiles reveal varied family arrangements, active campus involvement, full study loads, and some engagement in drinking and smoking. Mental health is mostly associated with cognition, with concerns including eating habits, sleep, medical issues, anxiety, and depression. Family-related stressors are primary, leading to emotion-focused coping strategies. Physical/social activities, education, and psycho-spiritual practices are suggested for promoting mental health on campus. The findings inform the development of mental health initiatives for the institution, emphasizing holistic well-being. The study findings indicate that mental health, as perceived by these students, predominantly revolves around cognitive aspects. Concerns encompass eating habits, sleep patterns, medical issues, anxiety, and depression. The primary stressors identified are related to family dynamics, leading students to employ emotion-focused coping strategies. To promote mental health on campus, students recommend a multifaceted approach encompassing increased participation in physical and social activities, heightened educational efforts and awareness, and the incorporation of psycho-spiritual practices. These insights serve as a foundation for the development of tailored mental health initiatives within the institution, emphasizing the holistic well-being of AIMS students.